Net Zero: useful target or unhelpful distraction? - Currall, James (International journal for the study of the Christian church, 2024)
The Environmental Crisis has been creeping up on us for years. Arguably this crisis arises from the abuse of God's creation, particularly from Western overconsumption and our consequently broken relationship with our neighbours worldwide and especially the poor and those in less developed parts of the world who are already suffering most from its consequences. Over the last five decades, prophetic voices have spoken of the dangers of environmental degradation and climate change. It is however only in the last few years that the narrower subject of climate change has become a prominent element of the discourse in the Western Church, though the situation is perhaps rather different in the Eastern Orthodox Church. Many organisations and indeed governments have set targets for Net Zero, but does this represent an appropriate and sufficient response for Churches? Is there a sound basis for such an approach, guided by our faith and theology?